STEM Education in Australia: Impediments and Solutions in Achieving a STEM-Ready Workforce - Brendan Bentley; Rob Sieben; Paul Unsworth (MDPI AG, 2022)
Recent government and industry priorities have led to a call to raise the quality of STEM learning to meet the future needs of industry and workforce skills. In Australia, education jurisdictions have responded to this challenge. Consequently, education is now considered critical in developing the skills required to meet these future needs. However, several significant issues have hindered STEM education's advancement. These impediments if not resolved may impact Australia's future STEM workforce and subsequent economic prosperity. This paper seeks to address some of the key impediments identified within the research literature by making a series of recommendations that provide insight into possible improvement to help recalibrate future STEM education initiatives and support Australia's long-term economic growth.